Evaluation of tumor-prostheses over time: Complications, functional outcome, and comparative statistical analysis after resection and reconstruction in orthopedic oncologic conditions in the lower extremities - Christina Enciso Holm; Michala Skovlund Soerensen; Müjgan Yilmaz; Michael Mørk Petersen (SAGE Open Medicine, 2022)
Objectives: Previous multicenter studies report variable outcomes and failure rates after tumor-prosthetic reconstructions. The purpose of this study was (1) to evaluate implant survival, limb survival, and functional outcome in a cohort of patients who underwent resection of primary malignancies or aggressive benign bone tumors and reconstruction with modern tumor-prostheses in the lower extremities and (2) to provide comparison to a historical cohort on previous generations of tumor-prostheses from the same center. Methods: A longitudinal retrospective single-center study of 72 consecutive patients (F/M = 30/42), mean age = 44 (range = 7–84) years with bone, soft tissue sarcoma adjacent to bone (n = 69), and aggressive benign bone tumors (n = 3) having surgery between 2006 and 2016 with bone resection and reconstruction with tumor-prostheses were compared to a historical cohort from1985 to 2005. Revisions were classified as major and minor revisions. Causes of failure were classified according to the Henderson classification. Fine and Gray competing risk analysis was used for assessing cumulative incidence for implant revision and limb amputation. Functional outcome was evaluated with Musculoskeletal Tumor Society Score system. Results: Forty-seven patients were alive at the end of the study. Mean follow-up was 6 years (range = 2–13 years). Ten-year cumulative risk of major revision was 18% (95% confidence interval = 9%–28%). Deep infection and recurrence of tumor caused most revisions in modern tumor-prostheses. Ten-year cumulative incidence of limb amputation was 11% (95% confidence interval = 3%–18%). According to the Henderson classification, the overall predominant failure mode was non-mechanical (n = 20, 51%). Mean Musculoskeletal Tumor Society Score was 20 (67%) (range = 0–30). Conclusion: A minimum of 2 years follow-up with modern modular tumor-prostheses demonstrated a relatively low risk of implant failure and amputation and also an acceptable functional outcome. No statistical difference of, implant survival, limb survival and functional outcome between tumor-prostheses over two time periods was observed, possibly explained by Type 2 error.